Evidence of Improvements to Arterial Stiffness Among Regular Users of Combustible Cigarettes – Effect of Inhalation of β-Caryophyllene: A Randomized, Double-Blind, Placebo-Controlled Study - Yamada Kazuya; Matahira Yoshiharu; Takuwa Nagisa; Yoshioka Yuri; Matsumura Shin-ichi; Higashihara Mayo; Zaima Nobuhiro; Unno Naoki (Contributions to Tobacco and Nicotine Research, 2025)
Nicotine consumption is known to be a risk factor for cardiovascular disease. β-Caryophyllene (BCP), a sesquiterpene with anti-inflammatory properties, was investigated in a randomized, double-blind, placebo-controlled trial to see if smoking cigarettes with BCP-containing capsules could improve aortic stiffness. In this study, 84 adult smokers were randomly assigned to either a BCP group or a placebo group. They smoked capsule-loaded cigarettes for 12 weeks, and various health parameters were measured every 4 weeks. The primary focus was on changes in brachial-ankle pulse wave velocity (baPWV), which measures arterial stiffness. The results showed that blood BCP levels increased only in the BCP group, while nicotine levels rose in both groups. For participants with a high baseline baPWV (≥ 1,400 cm/s), significant reductions in baPWV were observed in the BCP group at weeks 4 and 8. Additionally, baPWV at week 4 was significantly lower in the BCP group compared to the placebo group. No adverse effects were reported. In conclusion, smoking BCP-containing cigarettes improved arterial stiffness in participants with high baseline baPWV without causing any adverse effects.